The stability research of complete hydraulic sections of mechanized roof support - Felonenko, S.V.; Gubkina, V.V. (Розробка родовищ, 2015)
Ways to improve the section sustainability of the complete mechanical hydraulic roof supports are analyzed. Theoretical and graphical relations of the stability margin sections for the complete roof supports in dependence with the extractive production angle while different motion schemes are obtained. Виконано аналіз напрямів підвищення стійкості секцій комплектного механізованого гідравлічного кріплення, одержано теоретичні та графічні залежності запасу стійкості секцій комплектного кріплення від кута нахилу добувної виробки при різних схемах їх переміщення. Выполнен анализ направлений повышения устойчивости секций комплектной механизированной гидравлической крепи, получены теоретические и графические зависимости запаса устойчивости секций комплектной крепи от угла наклона очистной выработки при различных схемах их передвижки.